Desert heat island study in winter by mobile transect and remote sensing techniques - SUN, Chen-Yi (Institutional Knowledge at Singapore Management University, 2009)
A familiar problem in urban environments is the urban heat island (UHI), which potentially increases air conditioning demands, raise pollution levels, and could modify precipitation patterns. The magnitude and pattern of UHI effects have been major concerns of a lot of urban environment studies. Typically, research on UHI magnitudes in arid regions (such as Phoenix, AZ, USA) focuses on summer. UHI magnitudes in Phoenix (more than three million population) attain values in excess of 5°C. This study investigated the early winter period—a time when summer potential evapotranspiration >250 mm has diminished to 8.0°C, comparable to summertime UHI conditions. Through analysis of the Oke (1998) weather factor ΦW, it was determined thermally induced nighttime cool drainage winds could account for inflating the UHI magnitude in winter.